LITERATUR REVIEW : KUALITAS HIDUP PASIEN LEUKEMIA - Arslan Kamil Aries; Budi Widyanto; Sudirman Sudirman (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Leukemia is a malignant disease that attacks the hematopoiesis system, causing uncontrolled blood cell proliferation. Quality of life is one indicator that can be used to see the welfare conditions of patients suffering from chronic diseases such as leukemia. This review literature aims to find out the factors that influence the quality of life of leukemia patients. Literature search through Google Scholar, EBSCO, Springer Link, Elsevier, Sage databases using keywords: factors, quality of life, leukemia. The journals taken have a range from 2018 to 2020, which are then filtered according to the inclusion criteria set by the author. The results of the review indicate that there are several factors that affect the quality of life in leukemia patients, namely the therapeutic treatment undertaken, the patient's environment, and the role of care giver. Proper management of leukemia patients will improve the quality of life of these patients, and vice versa.